Recent Advances in Amide Reductions - Chardon, Aurélien; Morisset, Eléonore; Rouden, Jacques; Blanchet, Jérôme (Synthesis, 2018)
This short review highlights recent advances in amide reductions. The last two years have witnessed important developments with milestones reached in catalytic hydrogenations and hydrosilylations. While metal-catalyzed processes still focus tremendous efforts from the scientific community, methodologies based on the metal-free hydrosilylation of amides have definitively joined the competition.1 Introduction2 Recent Use of Stoichiometric Reducing Reagents3 Hydrogenations4 Hydrosilylations5 Conclusion and Outlook
Keywords: amides; hydrides; reduction; hydrogenation; hydrosilylation